Troubleshooting do Transporte Pneumático de pó de PEAD - César, Inês de Jesus Nogueira (2024)
The Pneumatic Powder Conveying System in section 80 of the HDPE plant was the Pneumatic Powder Conveying System in section 80 of the high-density polyethylene (HDPE) plant was refurbished between 1990 and 1991 to transport up to 20 t/h. The powder is carried from the drying hopper (Purge Bin H-3081) to Silos H-8001/2 using nitrogen in a closed circuit, with automatic oxygen and hydrocarbon control. Transport is carried out by C-8001 Blowers, and there are filters to protect the compressors. Finally, there is an exchanger in the system to prevent overheating. The aim of this work is to study the root causes that can lead to the plant being shut down or to a reduction in operating flow. the “5 Whys?” quality method was used. The novelty of this work lies in the fact that it is an exhaustive analysis identifying root causes and proposing solutions with an economic analysis of each one, something that has never been done for the company's pneumatic conveying system. Out of a total of twenty-four potential root causes, six were identified for the problem highlighted: No level in the Purge Bin; accumulation of polymer “webs” / “splinters”; the filters in the S-8012 Bag Filter are damaged; the flow interval is lower than recommended; ineffective washing of the E-8004 exchanger; lack of an exchanger upstream of the C-8001 Blowers. Seven proposals for improvement were put forward, three of which are of no cost to the company and can be implemented immediately: operating with the level in the Purge Bin; regularized inspection of the filters in the S-8012 Bag Filter; regularized checking of the nitrogen injection flow rate in the lubrication system of the V-8001 Rotary Valve. Of all the proposals for improvement, four require investment on the part of the company: chemical cleaning; recommissioning of the E-8003 exchanger; purchase of a flanged exchanger to replace the E-8003; round vibrating screen. Each of the recommendations has a benefit for the company of around 1 million euros per year. In addition, laboratory tests were carried out to see if there was any relationship between the grids and the pneumatic conveying failures.